(untitled) - Holmes, Erskine J. (Cambridge, United Kingdom, 2008)
Interpretation of Emergency Head CT is an invaluable quick reference to the key aspects of the head CT. It provides the clinician with an easy-to-use ‘ABCs’ system to analyze any head CT scan that may be encountered in the acute setting. The first section contains a comprehensive section on radiological anatomy of the brain and cranial anatomy, showing cranial anatomy on actual CT images. The details of the CT imaging process are also covered in a straightforward manner. The second section discusses a wide gamut of conditions that are likely to be encountered in acute medical practice. Pitfalls are highlighted and tips are included to assist the clinician in recognition of important signs, along with ways to distinguish other pathologies with a similar appearance. This is an excellent practical resource for all clinicians who utilize CT scans of the head as part of their patient management.
Keywords: Bộ não,Brain; Chẩn đoán hình ảnh,Diagnostic imaging